The - edited by Daniele Archibugi and Bengt-àke Lundvall (Oxford University Press, 2001)
Knowledge is becoming increasingly important in contemporary economic systems, and economic growth and welfare depends on how promptly economic agents are able to exploit the benefits derived from technological innovations. In a landscape characterized by globalization, the contributors to this volume offer a new perspective on the transformation undertaken by firms, universities, and other agents. They urge for a wider involvement of public policies to foster learning and innovation